Perancangan Media Komunikasi Visual Pada Museum Uang Sumatera - Arif Budiman; PG. Wisnu Wijaya (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2019)
The Sumatran Money Museum (MUS) in Medan, North Sumatra is one of the self-managed museums, with a collection of thematic and distinctive artifacts, namely the Sumatran currency! The official currency that was issued after independence in 1947-1949. This is among MUS's strengths. However, the problem that arises is that MUS has not yet maximally arranged aspects of visual communication such as consistency in implementing corporate identity, stationary, and graphic signaling (sign system), including the absence of graphic information (infographic) information on the history of the Sumatran currency. This study provides solutions to problem solving through designing a visual communication media based on identity (brand identity) and prioritizing informationfriendly principles, especially for young millennials. The problem in this study was answered by using the design method by following the stages of the graphic design process from Amy E. Arntson namely Research, Thumbnails; Roughs, Comprehensives and Ready for Press. The solution obtained from this research is to design a corporate identity service. Consists of the logo, stationary, merchandise and graphic information of the museum. As a first step in building the MUS brand identity.